1975
DOI: 10.1042/cs0490507
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indomethacin and Prostaglandin (PGE2) on Renal Failure Due to Glycerol in Saline-Loaded Rats

Abstract: 1. Acute renal failure was induced in conscious rate by subcutaneous injection of glycerol. 2. Expansion of the extracellular space by infusion of 150 mmol/l sodium chloride (saline) partly protected the animals against acute renal failure. 3. This protective effect of saline infusion disappeared when the animals were treated with indomethacin. This effect could be reversed by the addition of prostaglandin (PGE2) to the saline infusion. 4. We suggest that prostaglandins may be involved in mediating the protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…When the platelets aggregate (by the increased TXA2 and the diminished PGE2 and 6kPGF)a production by CsA) (table 2) and liberate their contents, the released 5-HT together with TXB2 (TXA2) contract the afferent arterioles resulting in decreased renal blood flow (RBF) and GFR, strongly implicated in the pathogenesis of CsA-induced nephrotoxicity [4,11,13]. Furthermore, chronic CsA administration was associated with irreversible structural changes [6] and/or hemolytic uremic syndrome [26].…”
Section: Effect O F Csa In Kts-pretreated Ratsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the platelets aggregate (by the increased TXA2 and the diminished PGE2 and 6kPGF)a production by CsA) (table 2) and liberate their contents, the released 5-HT together with TXB2 (TXA2) contract the afferent arterioles resulting in decreased renal blood flow (RBF) and GFR, strongly implicated in the pathogenesis of CsA-induced nephrotoxicity [4,11,13]. Furthermore, chronic CsA administration was associated with irreversible structural changes [6] and/or hemolytic uremic syndrome [26].…”
Section: Effect O F Csa In Kts-pretreated Ratsmentioning
confidence: 99%
“…In previous studies it has been found that infusion of PGs [13][14][15][16] or inhibition ofTXA2 synthesis [10][11][12] pro tected against the development of ARF. Because CsA enhanced TXB2 (TXA2) and diminished PGs, we ex pected the NT induced by this agent to be more serious than that induced by substances such as glycerol (GRL) [10,11], mercuric chloride (MC) [24] and gentamicin (GM) [12] which were found to enhance both TXA2 and PG production.…”
Section: Effect O F Csa In Normal Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…This property of prostaglandins has been termed cytoprotection (Chaudhury & Jacobson, 1978), although more properly it should be described as organoprotection (Szabo & Szelenyi, 1987). It is now known that the cytoprotective effects of prostaglandins extend to tissues other than the stomach, including the heart (Lefer et al, 1978;Ferrari et al, 1989), pancreas (Manabe & Steer, 1980), kidney (Papanicolaou et al, 1975;Ruwart et al, 1981) and liver (Stachura et al, 1980). It is likely that in many of these tissues cytoprotection is by a different, or additional mechanism, from that which operates in the stomach.…”
Section: Introductionmentioning
confidence: 99%